Genome-Wide Identification of Rapid Alkalinization Factor Family in Brassica napus and Functional Analysis of BnRALF10 in Immunity to Sclerotinia sclerotiorum - He, Yu-Han; Zhang, Zhuo-Ran; Xu, You-Ping; Chen, Song-Yu; Cai, Xin-Zhong (Frontiers in Plant Science, 2022)
Rapid alkalinization factors (RALFs) were recently reported to be important players in plant immunity. Nevertheless, the signaling underlying RALF-triggered immunity in crop species against necrotrophic pathogens remains largely unknown. In this study, RALF family in the important oil crop oilseed rape (Brassica napus) was identified and functions of BnRALF10 in immunity against the devastating necrotrophic pathogen Sclerotinia sclerotiorum as well as the signaling underlying this immunity were revealed. The oilseed rape genome carried 61 RALFs, half of them were atypical, containing a less conserved YISY motif and lacking a RRXL motif or a pair of cysteines. Family-wide gene expression analyses demonstrated that patterns of expression in responsive to S. sclerotiorum infection and DAMP and PAMP treatments were generally RALF- and stimulus-specific. Most significantly responsive BnRALF genes were expressionally up-regulated by S. sclerotiorum, while in contrast, more BnRALF genes were down-regulated by BnPep5 and SsNLP1. These results indicate that members of BnRALF family are likely differentially involved in plant immunity. Functional analyses revealed that BnRALF10 provoked diverse immune responses in oilseed rape and stimulated resistance to S. sclerotiorum. These data support BnRALF10 to function as a DAMP to play a positive role in plant immunity. BnRALF10 interacted with BnFER. Silencing of BnFER decreased BnRALF10-induced ROS production and compromised rape resistance to S. sclerotiorum. These results back BnFER to be a receptor of BnRALF10. Furthermore, quantitative proteomic analysis identified dozens of BnRALF10-elicited defense (RED) proteins, which respond to BnRALF10 in protein abundance and play a role in defense. Our results revealed that BnRALF10 modulated the abundance of RED proteins to fine tune plant immunity. Collectively, our results provided some insights into the functions of oilseed rape RALFs and the signaling underlying BnRALF-triggered immunity.